Intensifikasi Pengolahan Limbah Cair Laboratorium Melalui Proses Koagulasi dan Adsorpsi Studi Pengolahan Limbah Cair Laboratorium dengan Metode Kombinasi Fisika-Kimia - Sufra, Rifqi; Panjaitan, Jabosar R.H; Alhanif, Misbahudin; Mustafa, Mustafa; Yusupandi, Fauzi; Adriansyah, Endi; Rahmadini, Gustia; Raqin, M. Rayhan; Herawati, Peppy; Suzana, Asih (Jurnal Talenta Sipil, 2024)
Laboratory is one of the generators of hazardous liquid waste derived from chemicals used in practice and research. The waste is very dangerous when discharged into the environment because of the pollutants it contains. Therefore, it is necessary to treat the waste before it is disposed of to minimize the impact of pollution caused by the waste. The study aims to compare the effectiveness of zeolite adsorbents and activated carbon in reducing COD, TSS, and Cr heavy metals. Waste treatment is carried out by coagulation and adsorption methods. The adsorption process is performed using two types of adsorbents: zeolite and activated carbon. This study was carried out by variing the mass of the adsorbents at the time of complaining for 120 minutes in batches. Variations in the masses of the used 3, 5, 7, and 10 grams of adsorbenes. The results of the study showed that the more adsorbanes used, the higher the reduction of pollutant levels. The use of 10 grams of activated carbon adsorbents can reduce TSS pollutants levels of 92%, COD 95%, Cr 65%, and pH 5,0-6,38.